Interdependence of Tourism and Traffic in Croatia - Perić, Teodor; Šantić, Žarko; Perić, Dean (Promet - Traffic&Transportation)
Economic characteristics of tourism as stimulating factorof economic development of individual counties are reflectedin the expansion of economic relations with foreign count1ies,in stimulating regional development, in opening of new workplaces,in additional marketing of products on the domesticmarket, in evaluation of cultural and hist01ical resources, etc.The interrelation between the traffic system and tourism resultsfrom the complexity of characteristics and functions ofthese two economic activities. Although traffic system regularlyappears as the factor of improving or limiting the developmentof tourism, their relation needs to be considered in fact in theirmutual interaction.Defining of the Croatian traffic policy regarding tourism requirements,can be considered according to certain trafficbranches but also according to specific requirements the touristdemand has on the traffic system. However, tourist demandneeds to be understood as a part of the overall demand on thetraffic system so that it can and has to be satisfied by the trafficsupply formed according to the overall traffic demand.